THE SUBJECTS IN THE SCENE: ANALYSIS OF THE TEMPERATURES OFURBAN TARGETS IN PRESIDENTE PRUDENTE/ SP - INTERPRETATION OF STREET SWEEPERS ON A DAILY BASIS - Mendes, Lidiana Pinho [UNESP]; Tommaselli, Jose Tadeu Garcia [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
To better understand and assess the relation between climate, labor and health, this article seeks to characterize Presidente Prudente / SP regarding its thermal characteristics, as well as to interpret this reality within the context of work routine in relation to exposure to atmospheric elements - public sweeping. To do that we took recourse to various theoretical references which discuss the urban climate, urban climate in Presidente Prudente / SP and bibliographies containing important crosscutting discussion about uneven climate experience. Interviews with individuals involved with the sweeping activity in the city were carried out based on specific questionnaires additionally, absolute temperature maps were developed from remote sensing for the whole year of 2017. We sought to rise questions that problematize the average temperatures of urban targets and the meaning of the variables for streets sweepers. The results indicated the existence of symptoms that may be related to constant exposure to higher temperatures
Keywords: Urban climate; Presidente Prudente/SP; Temperatures Maps; Radiation; Street sweepers